2017
DOI: 10.1126/sciadv.1700841
|View full text |Cite
|
Sign up to set email alerts
|

Bication lead iodide 2D perovskite component to stabilize inorganic α-CsPbI 3 perovskite phase for high-efficiency solar cells

Abstract: A facile preparation of phase-stable cesium lead triiodide perovskite for high-performance solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
550
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 608 publications
(565 citation statements)
references
References 39 publications
11
550
1
3
Order By: Relevance
“…In addition to '2 × 2' corrugated 2D structure, this family has been extended to '3 × 3' [109] (Figure 6(b)) and '4 × 4' [110] types. More recently, corrugated-2D perovskites have been used to stabilize the α-CsPbI 3 phase and achieve a record PCE of 11.8% by connecting α-CsPbI 3 crystallites for effective electron transfer and passivating the surface defects [111].…”
Section: Corrugated-2d Organic Metal Halide Hybridsmentioning
confidence: 99%
“…In addition to '2 × 2' corrugated 2D structure, this family has been extended to '3 × 3' [109] (Figure 6(b)) and '4 × 4' [110] types. More recently, corrugated-2D perovskites have been used to stabilize the α-CsPbI 3 phase and achieve a record PCE of 11.8% by connecting α-CsPbI 3 crystallites for effective electron transfer and passivating the surface defects [111].…”
Section: Corrugated-2d Organic Metal Halide Hybridsmentioning
confidence: 99%
“…[17] Meanwhile, the past decade has witnessed unprecedented success of organicinorganic hybrid perovskites in PV applications, with the reported PCE of perovskite solar cells exceeding 23%. [29][30][31][32][33][34][35][36][37][38] Among these all-inorganic perovskite materials, α-CsPbI 3 exhibits an ideal optical bandgap (E g ) of 1.73 eV for PV applications. [29][30][31][32][33][34][35][36][37][38] Among these all-inorganic perovskite materials, α-CsPbI 3 exhibits an ideal optical bandgap (E g ) of 1.73 eV for PV applications.…”
mentioning
confidence: 99%
“…[47] Recently, Ma and co-workers pointed that Yb doping can reduce the number of defects and trap states, and obtained high PCE of 14.1%. [52] Zhao and co-workers employed ethylenediamine cations (EDA 2+ ) as 2D barrier molecule into α-CsPbI 3 and achieved a PCE of 11.8% with excellent thermal stability; [53] Huang and co-workers found that mixing a small amount of sulfobetaine zwitterions in α-CsPbI 3 could stabilize the phase and obtained PCE of 11.4%; [54] These results indicate quasi-2D structure could achieve efficient and stable CsPbI 3 PSCs in the future, but their PCE should be further enhanced. Finally, a PCE of 13.4% is achieved.…”
mentioning
confidence: 99%